Radiotherapy plus anti-PD1 versus radiotherapy for hepatic toxicity in patients with hepatocellular carcinoma - Rui-Jun Zhang; Hong-Mei Zhou; Hai-Yan Lu; Hong-Ping Yu; Wei-Zhong Tang; Mo-Qin Qiu; Liu-Ying Yan; Mei-Ying Long; Ting-Shi Su; Bang-De Xiang; Mei-Ling He; Xiao-Ting Wang; et al. (Radiation Oncology, 2023)
Abstract Purpose In this study, we aimed to compare the radiation-induced hepatic toxicity (RIHT) outcomes of radiotherapy (RT) plus antibodies against programmed cell death protein 1 (anti-PD1) versus RT alone in patients with hepatocellular carcinoma (HCC), evaluate prognostic factors of non-classic radiation-induced liver disease (ncRILD), and establish a nomogram for predicting the probability of ncRILD. Patients and methods Patients with unresectable HCC treated with RT and anti-PD1 (RT + PD1, n = 30) or RT alone (n = 66) were enrolled retrospectively. Patients (n = 30) in each group were placed in a matched cohort using propensity score matching (PSM). Treatment-related hepatotoxicity was evaluated and analyzed before and after PSM. The prognostic factors affecting ncRILD were identified by univariable logistic analysis and Spearman’s rank test in the matched cohort to generate a nomogram. Results There were no differences in RIHT except for increased aspartate aminotransferase (AST) ≥ grade 1 and increased total bilirubin ≥ grade 1 between the two groups before PSM. After PSM, AST ≥ grade 1 occurred more frequently in the RT + PD1 group (p = 0.020), and there were no significant differences in other hepatotoxicity metrics between the two groups. In the matched cohort, V25, tumor number, age, and prothrombin time (PT) were the optimal prognostic factors for ncRILD modeling. A nomogram revealed a good predictive performance (area under the curve = 0.82). Conclusions The incidence of RIHT in patients with HCC treated with RT + PD1 was acceptable and similar to that of RT treatment. The nomogram based on V25, tumor number, age, and PT robustly predicted the probability of ncRILD.